Work Life Balance: Qualitative Study on the Dual Role of Working Graduate Student - Yoppy Martha Aditya; Ovalia Rukmana (CV. Publikasi Indonesia, 2026)
This research aims to determine the extent of stress experienced by graduate students while working, spending time with family, and attending classes, as well as to explore various strategies to cope with the stress they face in managing multiple roles. A qualitative research method was used for this study. Data were collected through interviews and observations. The participants in this study were graduate students who were employed. The collected data were analyzed and conclusions were drawn. The research findings on stress related to the dual roles of work, family, and academic studies experienced by graduate students include academic pressures such as course materials, assignments, class schedules, time allocated for assignments, tuition fees, missed class information, forgetting to complete assignments, and knowledge-related issues. Meanwhile, pressures in the workplace include a high volume of work, complex tasks requiring extra mental effort, short deadlines, inadequate facilities and infrastructure, unsuitable leadership, and difficult coworkers. Additionally, simultaneously juggling multiple roles creates its own pressures, such as the need to complete work and academic tasks at the same time. Various strategies employed by graduate students in managing dual roles aim to minimize stress, resolve conflicts, and help students achieve their desired goals. These strategies are tailored to the type of stress present. Furthermore, each issue requires its own unique resolution, as no two problems are the same.